2009
DOI: 10.1186/1475-2875-8-251
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium falciparum exposure in utero, maternal age and parity influence the innate activation of foetal antigen presenting cells

Abstract: BackgroundMalaria in pregnancy is associated with immunological abnormalities in the newborns, such as hampered T-helper 1 responses and increased T-regulatory responses, while the effect of maternal Plasmodium falciparum infection on foetal innate immunity is still controversial.Materials and methodsThe immunophenotype and cytokine release by dendritic cells (DC) and monocytes were evaluated in cord blood from 59 Beninese women with or without malaria infection by using flow cytometry.ResultsAccumulation of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
39
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 48 publications
1
39
0
Order By: Relevance
“…Interestingly, HLA-DR expression of APCs was reported to correlate with infection status, 31 including in neonates exposed to malaria prenatally. 32 Furthermore, enhanced baseline expression of the inhibitory markers ILT3 and ILT4 on monocytes of PNG neonates might also suggest enhanced potential for tolerogenic activity. PNG ILT3 1 ILT4 1 monocytes coexpressed high levels of HLA-DR, suggesting that cells with potential inhibitory function were those that had been activated in utero.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, HLA-DR expression of APCs was reported to correlate with infection status, 31 including in neonates exposed to malaria prenatally. 32 Furthermore, enhanced baseline expression of the inhibitory markers ILT3 and ILT4 on monocytes of PNG neonates might also suggest enhanced potential for tolerogenic activity. PNG ILT3 1 ILT4 1 monocytes coexpressed high levels of HLA-DR, suggesting that cells with potential inhibitory function were those that had been activated in utero.…”
Section: Discussionmentioning
confidence: 99%
“…The choice of stimulants reflects a desire, based on our own knowledge and experience (32), to focus as much as possible on DC-mediated activity.…”
Section: Methodsmentioning
confidence: 99%
“…In the context of pregnancy, we and others have shown that placental infection with P. falciparum at delivery is associated with altered fetal innate immune responses, modified frequency of cord blood DC (31), partial activation of cord blood APC (32), and modulated cord blood cytokine responses to TLR ligation (33). Two independent studies in nonpregnant individuals have reported the capacity of P. falciparum infection to cause proinflammatory priming of responses to subsequent TLR ligation, a capacity that distinguishes the parasite from most other microbial pathogens (34,35).…”
mentioning
confidence: 99%
“…18 For this study, 352 pregnant women were enrolled at delivery after informed consent was obtained from July of 2006 to January of 2007 from the Hospital Mother and Child Lagune, the main obstetrical referring hospital in Cotonou, Benin and the Houenoussou Health Center in Cotonou, Benin. Women who underwent delivery at the above-mentioned clinics between July of 2006 and January of 2007 were enrolled in the study, regardless of presence or absence of fever or other symptoms.…”
mentioning
confidence: 99%